2013
DOI: 10.3727/096368912x657846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin C on Cytotherapy-Mediated Muscle Regeneration

Abstract: Skeletal muscles are the largest organs in the human body, and several therapeutic trials have been conducted that included stem cell transplantation to regenerate damaged or wasted muscles. It is well known that it is essential to make a favorable microenvironment (stem cell niche) to induce the proper differentiation of the transplanted stem cells. Some drugs, such as losartan (angiotensin II type I blocker), enhance the therapeutic effects of transplanted stem cells by inhibiting fibrosis. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have revealed that vitamin C promoted tendon healing by stimulating extracellular matrix remodeling as a precursor of collagen synthesis (18,19). In addition, vitamin C increased the therapeutic effects of combination stem cell therapy in a muscle laceration model (20). However, there has been no study as far as we are aware on the therapeutic effects of combination stem cell therapy and vitamin C administration on tendinopathy.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Previous studies have revealed that vitamin C promoted tendon healing by stimulating extracellular matrix remodeling as a precursor of collagen synthesis (18,19). In addition, vitamin C increased the therapeutic effects of combination stem cell therapy in a muscle laceration model (20). However, there has been no study as far as we are aware on the therapeutic effects of combination stem cell therapy and vitamin C administration on tendinopathy.…”
mentioning
confidence: 77%
“…However, there has been no study on co-administration of stem cell therapy with a particular compound (e.g. vitamin C or losartan) known to improve the stem cell niche in tendinopathy (20,31). The aim of this study was to determine the combined effects of stem cell therapy and vitamin C in the treatment of tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Recent studies also demonstrate that VC is associated with epigenetic reprogramming [22][23][24] and muscle regeneration. [25][26][27] Besides, VC has been widely used in the ex vivo culture of various cell types such as cardiac progenitor cells, 28 osteoblasts, 29 and induced pluripotent stem cells. 30 However, the effect of VC on the ex vivo proliferation and differentiation of MuSCs has not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that investigated the effect of AA deficiency on skeletal muscle in senescence marker protein-30 knockout mice, it was found that the cross-sectional area of muscle was significantly smaller in the AA deficiency group compared with the AA-treated group (1.5 g/L) (25). In the animal study that examined the effect of vitamin C on muscle renewal in the case of cytotherapy, it was observed that vitamin C enhanced muscle tissue collagen type I expression (17). However, in our study, AA administration did not show a significant effect on collagen type I levels at the dose and time administered.…”
Section: Discussionmentioning
confidence: 99%